The Role of Universities in Sustainable Transformation - Todorović, Brankica (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Achieving academic excellence requires exceptional dedication, long-term work, and continuous education. The synergy with new techniques, technologies, and trends, the dissemination of knowledge, the development of new curricula, and universities as drivers of innovation are part of the helix model. Universities should provide knowledge and contribute to the development of skills for applying digital transformation and AI. Education for sustainable development should be one of the main priorities in line with SDG 4, which focuses on quality education. The objectives of the research in this paper are:The significance of universities and the key components of their contribution to achieving the SDGs,The contribution of universities to achieving SDG 4, andA comparative analysis of implemented activities and programs that promote learning about sustainable development and digital transformation: Faculty of Contemporary Arts, Serbia, and Faculty of Economics and Business, Maribor.The methodological framework of the research is based on a qualitative approach through the use of a case study, which enables an in-depth analysis of educational practices and management strategies, in the context of education for sustainable development within specific higher education institutions.